Formation of the First Stars and Blackholes. Issue Volume 12:Issue S333(2017) (8th May 2018) - Yoshida, Naoki
Abstract: Cosmic reionization is thought to be initiated by the first generation of stars and blackholes. We review recent progress in theoretical studies of early structure formation. Cosmic structure formation is driven by gravitational instability of primeval density fluctuations left over from Big Bang. At early epochs, there are baryonic streaming motions with significant relative velocity with respect to dark matter. The formation of primordial gas clouds is typically delayed by the streaming motions, but then physical conditions for the so-called direct collapse blackhole formation are realized in proto-galactic halos. We present a promising model in which intermediate mass blackholes are formed as early as z = 30.